The subprime virus reckless credit, regulatory failure, and next steps - Engel, Kathleen C.; McCoy, Patricia A. 1954- (Oxford University Press, 2011)
In this lively new book, Kathleen C. Engel and Patricia A. McCoy tell the full story behind the subprime crisis. The authors, experts in the law and economics of financial regulation and consumer lending, offer a sharply reasoned, but accessible account of the actions that produced the greatest economic collapse since the Great Depression